Quality Control Batubara Dari Channel-pit Menuju Rom Stockpile di PT Mega Multi Energi - Suratno; Nurul Wahidah; Robby Nikolus (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
In processing existing data by analyzing the situation in the field from primary and secondary data. For primary data such as field observations, and coal sampling data and secondary data in the form of research location maps and laboratory test results, where the results of the coal quality laboratory test produced proximate analysis data with parameters of total moisture, inherent moisture, ash contant, volatile matter, fixed carbon, total sulphure and calorific value. In statistics, regression analysis is often used to test the relationship between an independent variable and a bound variable. The mathematical model that states the relationship between the two variables is called a regression equation. From the results of the comparison of coal quality with the parameters of proximate analysis, there was a change in coal quality at the time of the front towards the stockpile, which was as follows: TM = 0.68 %, IM = 0.61%, ASH = --1.32%, VM = 3.28 %, FC = 2.31 %, TS = -0.27 %, CV = -174 Kcal/kg. From the results of the analysis, it is known that the largest influence of the parameters that cause the decrease in calories is ash content of 36.69%, total moisture of 22.6%, volatile matter of 64.19%, inherent moisture of 27.5%, fixed carbon of 25.87%, and total sulfur of 0.44%.